SINQWAIN METHOD IN TEACHING RUSSIAN LANGUAGE (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article provides data on the translation of the Russian language in the areas of agronomy. To improve the conduct of classes and the development of oral speech, use a new pedagogical methodology, SINQWINE technology.